Synthesis, crystal structures and antimicrobial activity of palladium metal complexes of sulfonyl hydrazone ligands - Tadavi, Samina Karimkha; Bendre, Ratnamala Subhash; Patil, Satish Vittal; Gaguna, Shubha; Rajput, Jamatsing Darbarsing (European Journal of Chemistry, 2020)
Palladium complexes of sulfonyl hydrazone based ligands have been prepared by refluxing with the corresponding ligands and Pd(II) salt in 2:1 ratio. The compounds have been characterized by FT-IR and UV-Vis spectroscopic methods. The crystal structure of the prepared palladium complexes has been determined by single-crystal X-ray crystallographic technique. Crystal data for C40H50N4O6PdS2 (PMHT-Pd(II) complex): triclinic, space group P-1 (no. 2), a = 7.1561(6) Å, b = 12.1300(11) Å, c = 12.6117(17) Å, α = 63.498(11)°, β = 86.694(9)°, γ = 81.451(7)° and Z = 1. The final R1 was 0.0699 (I > 2σ(I)) and wR2 was 0.1834 (all data). Crystal data for C36H42N4O6PdS2 (PTHC-Pd(II) complex): monoclinic, space group P21/n (no. 14), a = 8.6726(2) Å, b = 20.8824(4) Å, c = 10.3351(2) Å, β = 104.429(2)° and Z = 2. The final R1 was 0.0344 (I > 2σ(I)) and wR2 was 0.0840 (all data). Crystal data for C36H42N4O6PdS2 (PTHT-Pd(II) complex): monoclinic, space group P21/n (no. 14), a = 9.7658(2) Å, b = 10.0488(3) Å, c = 18.7714(4) Å, β = 99.602(2)° and Z = 2. The final R1 was 0.0334 (I > 2σ(I)) and wR2 was 0.0832 (all data). Crystal data for C40H50N4O6PdS2 (PMHC-Pd(II) complex): triclinic, space group P-1 (no. 2), a = 10.2070(9) Å, b = 12.1841(13) Å, c = 16.8879(19) Å, α = 109.005(6)°, β = 90.061(5)°, γ = 99.032(5)° and Z = 2. The final R1 was 0.0822 (I > 2σ(I)) and wR2 was 0.2293 (all data). The single-crystal structure data showed a good agreement with the experimental results. The synthesized complexes were screened for their in vitro antibacterial activity against one Gram-negative (Escherichia coli) and two Gram-positive (Bacillus subtilis and Staphylococcus aureus) bacterial strains and for in vitro antifungal activity against Aspergillus niger, Aspergillus flavus and Aspergillus fumigatus. The PTHC-Pd(II) complex possesses the nearby significant antifungal activity analogous to the standard drug fluconazole against selected fungal strains Aspergillus niger, Aspergillus Flavus and Aspergillus fumigatus as well as the same complex showed the antibacterial activity for Staphylococcus aureus as comparable to standard ofloxacin drug.